URINARY SYSTEM INFECTION IN CHILDREN: CLINICAL COURSE, DIAGNOSTICS, TREATMENT - N.I. Bagirova; V.I. Kirillov (Union of pediatricians of Russia, 2008)
The article highlights one of the most frequent children's microbial and inflammatory diseases - a urinary system infection. The authors discuss the issues of etiopathogenesis, clinical manifestations and diagnostics of this pathology. They also share their own experience in treatment of the excretory tract infections.Key words: urinary tracts infection, clinical picture, diagnostics, treatment, children.